2016
DOI: 10.3233/bir-15085
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte arrest: Biomechanics and molecular mechanisms of β 2 integrin activation

Abstract: Integrins are a group of heterodimeric transmembrane receptors that play essential roles in cell–cell and cell–matrix interaction. Integrins are important in many physiological processes and diseases. Integrins acquire affinity to their ligand by undergoing molecular conformational changes called activation. Here we review the molecular biomechanics during conformational changes of integrins, integrin functions in leukocyte biorheology (adhesive functions during rolling and arrest) and molecules involved in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 277 publications
(279 reference statements)
0
47
0
1
Order By: Relevance
“…Talin is necessary for unbending of the two β2 integrin subunits [33]. Kindlin-3 binds CD18 as well [34], and both Talin and Kindlin-3are required for the induction of a high affinity state of the β2 integrin [35]. Talin is necessary and sufficient to induce an intermediate state of β2 integrin affinity and to confer slow rolling of PMN on endothelium [36].…”
Section: Activation Of β2 Integrinsmentioning
confidence: 99%
“…Talin is necessary for unbending of the two β2 integrin subunits [33]. Kindlin-3 binds CD18 as well [34], and both Talin and Kindlin-3are required for the induction of a high affinity state of the β2 integrin [35]. Talin is necessary and sufficient to induce an intermediate state of β2 integrin affinity and to confer slow rolling of PMN on endothelium [36].…”
Section: Activation Of β2 Integrinsmentioning
confidence: 99%
“…Similar to α4β1, the β2-integrins, also called leukocyte integrins, are indispensable for tissue immigration [27,79,89,90]. Unlike other integrins, they have only few ECM ligands since their main function is to enable adhesion to other cells through binding to members of the IgCAM superfamily, e.g., ICAMs, VCAMs or JAMs.…”
Section: β2-integrinsmentioning
confidence: 99%
“…These integrins, like 2 others, are heterodimeric glycoproteins that exist in four forms on the PMN. Each displays a unique α-subunit (CD11a, b, c, or d) and an identical β-subunit (CD18) 101 . The epithelial counter-receptor for PMN β2 integrins remains elusive, and functional mapping studies of this β2 integrin-dependent pathway has suggested that the profile of inhibition is distinct from that of other known ligands of CD11b/CD18 94 .…”
Section: Epithelial Endpoint Responses To Cytokinesmentioning
confidence: 99%